Treatment of Chemotherapy-Induced Anemia in Ovarian Cancer Patients: Does the Use of Erythropoiesis-Stimulating Agents Worsen Survival?. Issue 5 (1st June 2012) - Rocconi, Rodney P.; Sullivan, Paula; Long, Beverly; Blaize, Marie; Brown, Jennifer; Arbuckle, Janeen; Bevis, Kerri; Estes, Jacob M.; Reed, Eddie; Finan, Michael A.
Abstract : Objective: Considering the paucity of data relating erythropoiesis-stimulating agent (ESA) use to ovarian cancer survival, our objective was to evaluate the effect of ESA as used for the treatment of chemotherapy-induced anemia (CIA) on survival in ovarian cancer patients. Materials and Methods: A multi-institution retrospective chart review was performed on ovarian cancer patients. Data collection included patient demographic, surgicopathologic, chemotherapy, ESA, and survival data. Patients were stratified by ever-use of ESA and were compared using appropriate statistical methods. Results: A total of 581 patients were eligible for analysis with 39% (n = 229) patients with ever-use of ESA (ESA-YES) and 61% (n = 352) never-use ESA (ESA-NO). Mean age was 60.4 years with most patients having stage IIIC (60%) of papillary serous histological diagnosis (64%) with an optimal cytoreduction (67%). Median follow-up for the cohort was 27 months. Both ESA-YES and ESA-NO groups were similar regarding age, body mass index, race, stage, histological diagnosis, and debulking status. Compared with the ESA-NO group, ESA-YES patients were significantly more likely to experience recurrence (56% vs 80%, P < 0.001) and death (46% vs 59%, P = 0.002). Kaplan-Meier curves demonstrated a significant reduction in progression-free survival for ESA-YES patients (16 vs 24 months, P < 0.001); however, overall survival was statistically similar between the 2 groups (38 vs 46 months, P = 0.10). When stratifying by ever experiencing a CIA, ESA-YES patients demonstrated a significantly worse progression-free survival (17 vs 24 months, P = 0.02) and overall survival (37 vs 146 months, P < 0.001). Conclusions: Our data evaluating the use of ESA as a treatment of CIA in ovarian cancer patients are similar to reports in other tumor sites. Considering that patients who used ESA were more likely to experience recurrence and death and to have decreased survival, the use of ESA in ovarian cancer patients should be limited.